Cg1246, a new player in mycolic acid biosynthesis in Corynebacterium glutamicum. Issue 4 (8th April 2022) - de Sousa-d'Auria, Célia; Constantinesco, Florence; Bayan, Nicolas; Constant, Patricia; Tropis, Maryelle; Daffé, Mamadou; Graille, Marc; Houssin, Christine
Abstract : Mycolic acids are key components of the complex cell envelope of Corynebacteriales . These fatty acids, conjugated to trehalose or to arabinogalactan form the backbone of the mycomembrane. While mycolic acids are essential to the survival of some species, such as Mycobacterium tuberculosis, their absence is not lethal for Corynebacterium glutamicum, which has been extensively used as a model to depict their biosynthesis. Mycolic acids are first synthesized on the cytoplasmic side of the inner membrane and transferred onto trehalose to give trehalose monomycolate (TMM). TMM is subsequently transported to the periplasm by dedicated transporters and used by mycoloyltransferase enzymes to synthesize all the other mycolate-containing compounds. Using a random transposition mutagenesis, we recently identified a new uncharacterized protein (Cg1246) involved in mycolic acid metabolism. Cg1246 belongs to the DUF402 protein family that contains some previously characterized nucleoside phosphatases. In this study, we performed a functional and structural characterization of Cg1246. We showed that absence of the protein led to a significant reduction in the pool of TMM in C. glutamicum, resulting in a decrease in all other mycolate-containing compounds. We found that, in vitro, Cg1246 has phosphatase activity on organic pyrophosphate substrates but is most likely not a nucleoside phosphatase. Using a computational approach, we identified important residues for phosphatase activity and constructed the corresponding variants in C. glutamicum . Surprisingly complementation with these non-functional proteins fully restored the defect in TMM of the Δ cg1246 mutant strain, suggesting that in vivo, the phosphatase activity is not involved in mycolic acid biosynthesis.